Mass attenuation coefficients and partial interactions of BaO-ZnO-B2O3 glasses system - Kothan S. (2017)
© 2016 Trans Tech Publications, Switzerland. The mass attenuation coefficients and partial interactions of BaO-ZnO-B 2 O 3 glasses have been investigated using WinXCom program at difference photon energy. BaO-ZnO-B 2 O 3 glasses were prepared in composition xBaO: 20ZnO: (80-x)B 2 O 3 (where x = 15 and 20 mol %) by melt quenching technique under normal atmosphere. The densities of glasses are 3.00 and 3.10 g/cm 3 , respectively. The mass attenuation coefficients at 20% mol are higher than 15% mol of BaO in all energy range. The optical spectra were measured and good transparent behavior was obtained. Half value layer (HVL) of glasses are also report and compared with same standard shielding materials and show better shielding than ordinary concrete.